Wolność wyboru w kreowaniu własnego stylu życia przez współczesną młodzież - Peret-Drążewska, Paulina (Studia Edukacyjne, 2020)
This article is dedicated to reflection on the lifestyle of contemporary young people, which is formed on the basis of freedom of choice. This is due to the specific nature of the globalized reality of sociocultural, in particular popular culture and consumerism, which are the main element of youth lifestyle emphasizing the role of unlimited possibilities in shaping their own identity and way of life of the elements that once were dependent mainly on class membership.